2021
DOI: 10.1038/s42003-021-02952-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and macroscopic architectures of intersubject functional variability in human brain white-matter

Abstract: Intersubject variability is a fundamental characteristic of brain organizations, and not just “noise”. Although intrinsic functional connectivity (FC) is unique to each individual and varies across brain gray-matter, the underlying mechanisms of intersubject functional variability in white-matter (WM) remain unknown. This study identified WMFC variabilities and determined the genetic basis and macroscale imaging in 45 healthy subjects. The functional localization pattern of intersubject variability across WM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…PNH features ectopic nodules located in the white matter that have been reported to have altered diffusion metrics 23 . Additionally, functional white matter activity and connectivity have been observed both at rest and during tasks 24–27 . However, the local functional neural basis of this disorder is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNH features ectopic nodules located in the white matter that have been reported to have altered diffusion metrics 23 . Additionally, functional white matter activity and connectivity have been observed both at rest and during tasks 24–27 . However, the local functional neural basis of this disorder is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Additionally, functional white matter activity and connectivity have been observed both at rest and during tasks. 24 , 25 , 26 , 27 However, the local functional neural basis of this disorder is not well understood. In our previous PNH‐related epileptic network investigation, we found that amplitude of low‐frequency fluctuations (ALFFs) had lower amplitude in default mode network (DMN) hubs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the white matter (WM) signal was regressed out to focus on the gray matter (GM) signals, which might be another limitation of our study. However, more and more evidence suggested brain white‐matter (WM) signals obtain using BOLD‐fMRI provide functional information about intrinsic activity and can be used to characterize its connectivity (Gong‐Jun Ji et al, 2017 ; Li et al, 2019 ; Li et al, 2021 ). A recent study has identified and replicated robust decreased small‐world topology in two completely independent samples of MDD.…”
Section: Discussionmentioning
confidence: 99%
“…noise, motion, scanner effects). Biological variance is at the heart of neuroimaging studies examining how variation and changes in macroscale brain structure and function relate to behaviour and disease [77][78][79].…”
Section: Variancementioning
confidence: 99%